Edukasi Dan Implementasi Aktivitas Fisik Sebagai Upaya Peningkatan Kesehatan Dalam Menghadapi Gejala Klimakterium Pada Ibu Premenopause Di Desa Dukuh, Kecamatan Bayat, Kabupaten Klaten - Devi Permatasari; Sri Sat Titi Hamranani; Aulia Happy (Universitas Muhammadiyah Klaten, 2024)
Premenopause is a transition from reproductive to non-reproductive starting at the age of 40-50 years. The climacterium is the 4-5 year period that occurs before menopause. Regular physical activity with a duration of more than 60 minutes can reduce climacteric symptoms. Efforts to improve the health of premenopausal mothers need to be made to reduce the impact of climacteric symptoms. Efforts to improve health can be carried out by promoting health regarding premenopause, climacteric symptoms and joint physical activity. Health promotion is intended to increase knowledge of the importance of physical activity in reducing premenopausal symptoms. Premenopausal mothers are also trained for physical activity by means of elderly exercise. The aim of this service is to increase the knowledge of premenopausal mothers in reducing climacteric symptoms with physical activity. And mothers are able to practice directly doing physical activities in the form of elderly exercise to improve health and fitness. Premenopausal mothers are also given health checks in the form of checking blood pressure, checking GDS and uric acid. The results of community service were an increase in the knowledge of premenopausal mothers after being given education about physical activity and the climacterium, namely good knowledge of 86%, and sufficient knowledge of 14%. All premenopausal mothers have carried out physical activity and health checks in the form of blood pressure, GDS checks, uric acid level checks, vital signs and maternal weight checks. The conclusion is that the majority of premenopausal mothers have good knowledge about the importance of physical activity and climacteric symptoms so that mothers can increase daily physical activity in preventing climacteric symptoms